Intraocular and plasma levels of cellular fibronectin in patients with uveitis and diabetes mellitus. Issue 5 (16th April 2004) - Probst, K; Fijnheer, R; Schellekens, P; Rothova, A
Abstract : Aim: To determine intraocular and plasma levels of cellular fibronectin (cFN) in patients with uveitis or diabetes mellitus (DM) and to assess the association with disease activity, macular oedema, and vascular leakage on fluorescein angiography. In addition, to examine whether cFN is locally produced in the eye. Methods: Intraocular and plasma levels of cFN were determined by ELISA in 39 patients with uveitis (23 active, 16 non-active), in 11 patients with DM (eight with and three without diabetic retinopathy) and in 17 control patients. The influence of diabetic retinopathy, inflammatory activity, vascular leakage, and macular oedema (MO) on intraocular and plasma cFN levels was studied. Local production of cFN was determined by calculating absolute and relative intraocular to plasma ratios. Aqueous and vitreous levels of cFN were compared. Results: No differences in plasma cFN levels were found between patients with uveitis, DM, or controls. Intraocular cFN levels were significantly raised in patients with uveitis and DM, specifically in those with active disease (active uveitis and active diabetic retinopathy versus controls: p = 0.001 and 0.002 respectively). Further, intraocular cFN levels were significantly elevated in patients with macular oedema or vascular leakage, irrespectively of whether associated with uveitis or DM (p = 0.001 and 0.002). Intraocular cFN levels were consistently higher in the vitreous than the aqueous. Intraocular production of cFN was documented by elevated absolute and relative intraocular to plasma ratios in nine out of 11 patients tested. Conclusions: Elevated intraocular cFN levels were found in uveitis and DM, especially in those with active processes, intraocular vascular damage, and MO. These results suggest that locally produced cFN levels reflect intraocular vascular damage.